2020
DOI: 10.3390/toxins13010019
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cardiac Effects of Venoms from Tentacles and the Bell of Live Carukia barnesi: Using Non-Invasive Pulse Wave Doppler

Abstract: Carukia barnesi was the first in an expanding list of cubozoan jellyfish whose sting was identified as causing Irukandji syndrome. Nematocysts present on both the bell and tentacles are known to produce localised stings, though their individual roles in Irukandji syndrome have remained speculative. This research examines differences through venom profiling and pulse wave Doppler in a murine model. The latter demonstrates marked measurable differences in cardiac parameters. The venom from tentacles (CBVt) resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…ECG changes and elevated cardiac marker levels have been reported in box jellyfish envenomation. [21][22][23][24] To date, no WPW changes on ECG have been documented in cases of jellyfish sting envenomation. The WPW feature in our patient appears to have persisted and therefore might have been pre-existing.…”
Section: Discussionmentioning
confidence: 99%
“…ECG changes and elevated cardiac marker levels have been reported in box jellyfish envenomation. [21][22][23][24] To date, no WPW changes on ECG have been documented in cases of jellyfish sting envenomation. The WPW feature in our patient appears to have persisted and therefore might have been pre-existing.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to cnidae, there is significant variation in venom profiles between cnidarian taxa ( Ashwood et al, 2020 ), but also intra-specifically both between and within geographic locations ( Mitchell et al, 2020 ; Winter et al, 2010 ; Yue et al, 2019 ). Furthermore, venom variation has also been shown to occur within different anatomical structures within individuals ( Klompen et al, 2018 ; Little et al, 2020 ; Macrander et al, 2016 ; Mies et al, 2017 ; Mitchell et al, 2017 ). This variation is believed to reflect the changes in the cnidom that arise due to specific ecological functions of different areas of the body ( Ashwood et al, 2020 ; Little et al, 2020 ; Prentis et al, 2018 ; Schendel et al, 2019 ).…”
Section: Cnidarian Venom Ecologymentioning
confidence: 99%
“…Furthermore, venom variation has also been shown to occur within different anatomical structures within individuals ( Klompen et al, 2018 ; Little et al, 2020 ; Macrander et al, 2016 ; Mies et al, 2017 ; Mitchell et al, 2017 ). This variation is believed to reflect the changes in the cnidom that arise due to specific ecological functions of different areas of the body ( Ashwood et al, 2020 ; Little et al, 2020 ; Prentis et al, 2018 ; Schendel et al, 2019 ). It has also been found that the composition of the venom within an individual may also vary between different nematocysts types ( McClounan and Seymour, 2012 ).…”
Section: Cnidarian Venom Ecologymentioning
confidence: 99%
“…Another dangerous jellyfish that can be found in tropical waters along the coasts of Australia is the Irukandji jellyfish (Carukia barnesi), a small species of the jellyfish which is the size of a human finger. Its sting can result in the Irukandji syndrome associated with catecholamine release [29,30]. A sting from cnidarian species can cause a variety of signs and symptoms, including the anaphylactic shock [31].…”
Section: Jellyfishes (Scyphozoa)mentioning
confidence: 99%